United States Air Force Defense Suppression Doctrine, 1968-1972 - Young, James L. Jr. (Kansas State University, 2008)
On March 30, 1972 the Democratic Republic of Vietnam (DRV) launched a conventional offensive, dubbed the Easter Offensive, against South Vietnam. In response to this act President Richard Nixon ordered the United States Air Force (USAF) and Navy (USN) to resume bombing North Vietnam. For the next nine months, USAF conducted offensive operations against the whole of the DRV in an attempt to accomplish four major objectives. First, USAF units sought to interdict sufficiently the North Vietnamese Army's (NVA's) supply lines to preclude continued conventional operations in South Vietnam. Second, President Nixon had directed the Air Force to inflict sufficient punishment on North Vietnam in order to deter further aggression against its southern neighbor. Third, as implied by the Nixon Doctrine, USAF was to establish convincingly its ability to conduct conventional operations in support of an allied nation during a major conflict. Finally, with the introduction of B-52 bombers in December 1972, the Air Force was to maintain the credibility of manned strategic aircraft as part of American nuclear deterrence policy. Historically, the United States Air Force and many civilian observers have maintained that the United States Air Force succeeded in all four tasks. However, the evidence strongly indicates that the United States Air Force not only failed to achieve all but the interdiction objective during the course of operations against North Vietnam, but that this defeat stemmed from the decision not to develop a comprehensive Suppression of Enemy Air Defense (SEAD) doctrine from 1968 through 1972. In choosing this course of action, USAF's military and civilian leaders guaranteed that American forces would be unable to bring sufficient force to bear to achieve President Nixon's goals. Furthermore, by choosing this course of action and, in addition, refocusing the Air Force on nuclear delivery rather than enhancing USAF's capability to penetrate an integrated air defense (IADS), these same leaders ignored the results of Operation Rolling Thunder. The consequence of this choice, as will be shown in the following pages, was an outcome that had serious implications for the United States' Cold War conventional and nuclear military policy.
Keywords: SEAD; United States Air Force; Vietnam; Linebacker; Lyndon Johnson; Wild Weasel; History, General (0578); History, Modern (0582); History, United States (0337)